IJMA’ DAN ISSU KOTEMPORER - AS, Susiadi (ASAS, 2014)
Abstrak: Ijma 'is a legal determination method that involves a lot of scholars to ensure accuracy, validity and force of law. Unfortunately, the requirements that scholars can be categorized as mujtahid in the past are now much different in quality and depth of knowledge. This raises a question whether the differences in the method of ijma 'should remain as it is or to be reconstructed to fit with the times. If the law must evolve with the times, the method of ijma' , then, should also be developed to be more accommodating to the various legal issues that arise in the future Keywords: ijma' as a method of legal determination